The moderating role of reporting quality - Cuny, Christine; Dube, Svenja (Contemporary Accounting Research, 2025)
This paper examines whether the sensitivity of local government credit ratings to external signals about the local economy varies with the quality of the governments' financial reports. We find the credit ratings of local governments that are required to comply with GAAP are less sensitive to changes in local home values than similarly affected governments that are not required to comply with GAAP. Further, we show that GAAP's moderating role increased after Governmental Accounting Standards Board (GASB) 34 substantially improved the quality of GAAP‐compliant governments' financial reports, which helps to attribute the main findings to reporting quality. To understand the mechanism, we study positive and negative economic signals separately. The results are pronounced when the change in home values is negative, consistent with reporting quality decreasing the rating agency's uncertainty about local governments' preexisting likelihood of default. We conclude that credit rating agencies are less sensitive to local economic signals when the local government's financial reports are of higher quality.